A Hierarchical Model for Evaluation and Treatment of Visual Perceptual Dysfunction in Adult Acquired Brain Injury, Part 1. - Warren, Mary (American Journal of Occupational Therapy, 1993)
A developmental framework for evaluation and treatment of visual perceptual deficits in adults with acquired brain injury is presented. The framework is based on a review of research conducted on post-cerebrovascular accident subjects and subjects with traumatic brain injuries. Visual perceptual skill is conceptualized as a hierarchy of skill levels that interact and subserve each other. Higher level skills evolve from integration of lower level skills and are subsequently affected by disruption of lower level skills. Oculomotor control, visual field, and acuity form the foundation skills, followed by visual attention, scanning, pattern recognition, memory, and visual cognition. Brain injury can affect the integrity and interaction of each skill level and affect daily living function. Application of this framework dictates a bottom-up approach to evaluation and treatment, emphasizing identification and remediation of deficits in lower level skills to allow normal integration of higher level skill.